Accessibility Model in Electronic Government: Evaluation of Brazilian Web Portals - Oliveira, Alberto; Souza, Eliane (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2017: Anais do XIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2017.6060, 2017)
The Brazilian federal government has promoted several actions towards addressing digital accessibility in e-government systems once it is essential for all citizens to take part on participatory digital governance and have access to important information and online services. In this paper, we evaluate the main web portals of 28 federal agencies with ministry status to check whether they comply with the main laws and standards related to digital accessibility, namely the Accessibility Model in Electronic Government, also known in Portuguese as e-MAG; the Digital Government Identity; and the Accessibility Circumstantial Report. Unfortunately, most federal agencies fail to deliver acceptable levels of accessibility and to present a digital accessibility assessment along with a work plan to address the known issues. We also present an interview with a blind citizen to understand the Brazilian digital accessibility scenario from the perspective of a person with disability. The results of the interview confirmed that, even with the existence of e-MAG, the Brazilian federal government has yet a long way to walk to assure citizens the basic rights to access information, online services and take part in important decisions.